A collaborative exercise on DNA methylation based body fluid typing. Issue 21 (19th September 2016) - Jung, Sang‐Eun; Cho, Sohee; Antunes, Joana; Gomes, Iva; Uchimoto, Mari L.; Oh, Yu Na; Di Giacomo, Lisa; Schneider, Peter M.; Park, Min Sun; van der Meer, Dieudonne; Williams, Graham; McCord, Bruce; et al.
Abstract : A collaborative exercise on DNA methylation based body fluid identification was conducted by seven laboratories. For this project, a multiplex methylation SNaPshot reaction composed of seven CpG markers was used for the identification of four body fluids, including blood, saliva, semen, and vaginal fluid. A total of 30 specimens were prepared and distributed to participating laboratories after thorough testing. The required experiments included four increasingly complex tasks: (1) CE of a purified single‐base extension reaction product, (2) multiplex PCR and multiplex single‐base extension reaction of bisulfite‐modified DNA, (3) bisulfite conversion of genomic DNA, and (4) extraction of genomic DNA from body fluid samples. In tasks 2, 3 and 4, one or more mixtures were analyzed, and specimens containing both known and unknown body fluid sources were used. Six of the laboratories generated consistent body fluid typing results for specimens of bisulfite‐converted DNA and genomic DNA. One laboratory failed to set up appropriate conditions for capillary analysis of reference single‐base extension products. In general, variation in the values obtained for DNA methylation analysis between laboratories increased with the complexity of the required experiments. However, all laboratories concurred on the interpretation of the DNA methylation profiles produced. Although the establishment of interpretational guidelines on DNA methylation based body fluid identification has yet to be performed, this study supports the addition of DNA methylation profiling to forensic body fluid typing.